2019
DOI: 10.1186/s13031-019-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of intimate partner violence against women in conflict affected northern Uganda: a cross-sectional study

Abstract: Background Intimate partner violence (IPV) is an important public health issue as it impacts negatively on health, economic and development outcomes. In conflict affected northern Uganda, IPV prevalence is high and additional context-specific risk factors exist. People residing in this region have been displaced, exposed to war and violence, and had livelihoods destroyed. There are few studies examining IPV in this setting. In this study we aim to further understand the prevalence of IPV towards w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 21 publications
7
48
2
Order By: Relevance
“…This study revealed that women who had a substance user (alcohol, chat, or cigarette) husband were three times greater to be violated compared to those women who had not substance user husbands. This finding is similar with the studies conducted in Awi Zone and western Ethiopia (Abeya et al, 2011;Semahegn et al, 2013), Uganda (Black et al, 2019), Nigeria (Ajala., 2017a), South Africa (Sania et al, 2017), Philippine , Eastern Saudi (N Pearce & Afifi., 2011), and Eastern Sudan (AbdelAziem et al, 2014. This could be justified by use of substances such as alcohol drinking, smoking or khat chewing can affect the thinking and cognitive potential of the users.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that women who had a substance user (alcohol, chat, or cigarette) husband were three times greater to be violated compared to those women who had not substance user husbands. This finding is similar with the studies conducted in Awi Zone and western Ethiopia (Abeya et al, 2011;Semahegn et al, 2013), Uganda (Black et al, 2019), Nigeria (Ajala., 2017a), South Africa (Sania et al, 2017), Philippine , Eastern Saudi (N Pearce & Afifi., 2011), and Eastern Sudan (AbdelAziem et al, 2014. This could be justified by use of substances such as alcohol drinking, smoking or khat chewing can affect the thinking and cognitive potential of the users.…”
Section: Discussionsupporting
confidence: 92%
“…The difference in the prevalence could be attributed to the differences in study periods, number of countries involved in the study and sample. The high prevalence of IPV in Uganda (44%) confirms the findings of studies on IPV that were conducted in Uganda ( Black et al, 2019 ; Gubi, Nansubuga, & Wandera, 2020 ; Prabhu et al, 2011 ). However, in these studies, the prevalence were higher than what was found in the current because the previous studies focused on lifetime experience of IPV, contrary to the past year experience of IPV in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…As a result of the post-conflict situation, Gulu region has a high prevalence of intimate partner violence [ 29 , 30 ]. Women discussed domestic violence, its root causes, and its consequences during their group meetings.…”
Section: Resultsmentioning
confidence: 99%